(untitled) (Global Journal of Management and Business Research, 2021)
Racial wealth disparities in US continues to persist despite community state and federal governments programs to arrest the slide Contemporary community wealth creation approaches using anchor institutions concepts to bridge the gap assumes the wealth improvement duality of the community and the anchor institution coming together with external agents of support